REVIEW OF THE REGULATORY FRAMEWORK FOR TRADE LIBERALISATION AND TRANSNATIONAL COOPERATION IN NIGERIA. - Akor, Ondale; Anokwuru, Faith Sandra (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Nigeria is one of the largest economies in Africa, with prospects for international trade and investments; and operating under the aegis of trade liberalisation as a national economic and investment policy. However, these potential are largely undermined by systemic policy failure, dysfunctional institutions and infrastructural deficit in the Nigerian economic and investment environment. Extant literature overwhelmingly emphasis the role of international trade to national development, with scant reference to the impact of trade liberalisation in promoting a competitive and transnational market economy in Nigeria. The study therefore, examines the regulatory framework on trade liberalisation and impact on investment dynamics and transnational market economy in Nigeria. The doctrinal method is adopted by the study with reliance on national laws on trade liberalisation, including the Constitution of the Federal Republic of Nigeria (CFRN) 1999. The CFRN provides for an open market economy with market liberalisation as the national economic policy, and serving as stimulant for competitive international trade and multilateral cooperation between Nigeria and the global community. The potential for competitive market economy that promotes investments and international trade; free movement of goods and services; exchange in knowledge and technology; direct foreign investments; with capacity for impacting positively on the national economy, are core incentives from trade liberalisation. The Nigerian liberalisation policy entrenches a solid framework for promoting investment dynamics and supranational cooperation, capable of engendering a competitive business clime that positively impacts on national development. In order for Nigeria to enjoy the economic potential under supranational cooperation, there is need for continuous reforms aimed at strengthening the regulatory and institutional frameworks on trade liberalisation, to align with standard global practices; and establishment of a functional dispute resolution mechanism, with underpinning for stabilizing market dynamics and changing the economic trajectory in Nigeria.